2014
DOI: 10.1111/phn.12128
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Risky Sexual Behaviors and Effective STI/HIV and Pregnancy Intervention Programs for African American Adolescents

Abstract: After analyzing six national intervention programs proven to be effective, the findings suggest that future prevention programs should be designed with more emphasis on avoidance or limited substance use, increased parental involvement, integration of cultural teaching components such as storytelling and history as suggested from the Aban Aya Youth Project. This study also concluded that future prevention programs should consider the length of programs be longer than 1 year, as it has been shown to be more eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 17 publications
4
31
0
9
Order By: Relevance
“…A negative association was found; adolescents with higher levels of parental monitoring reported lower levels of adolescent sexual risk behaviors. These findings are supported by prior research conducted by Lee et al (2014) and Nappi et al (2008), both of which emphasized the significant moderating impact of parental monitoring on sexual risk in adolescence.…”
Section: Chapter V Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A negative association was found; adolescents with higher levels of parental monitoring reported lower levels of adolescent sexual risk behaviors. These findings are supported by prior research conducted by Lee et al (2014) and Nappi et al (2008), both of which emphasized the significant moderating impact of parental monitoring on sexual risk in adolescence.…”
Section: Chapter V Discussionsupporting
confidence: 85%
“…In the current study, parental monitoring refers to the parent's knowledge of the adolescent's whereabouts and establishment of boundaries and rules which the adolescent must adhere to. There has been substantial research to support that parental monitoring is related to reducing risk behaviors in African American adolescents (Yang et al, 2007;Nappi et al, 2008;DiClemente, Crosby & Salzar, 2006 (Lee, Cintron & Kocher, 2014).…”
Section: African-american Parental Monitoring Of Adolescentsmentioning
confidence: 99%
“…Despite the more clear focus on marginalized populations within human rights reviews, reviews with a focus on lesbian, gay, bi-sexual, or transgender individuals were not found suggesting both a heteronormative lens to the existing research base and the invisibility of gender expressions that differ from the cultural norm. Additionally, while four reviews addressed adolescents, two of which focused exclusively on this population (one on African American youth and another on Latino youth in the US and Mexico)[14, 15, 17, 24], concentration on this population, which often faces stigma and discrimination in SRH service provision, was still relatively rare.…”
Section: Resultsmentioning
confidence: 99%
“…Adolescent sexual behaviour is influenced by multiple, complex sets of factors and determinants [7][8][9][10][11][12]. Adolescents in Saudi Arabia face immense challenges due to increasing globalisation, urbanisation, digital communications, economic challenges, and other external forces; and like other adolescents, they are approaching adulthood in a world that is vastly different from that of previous generations [13].…”
Section: Introductionmentioning
confidence: 99%